Preparation and Characterisation of Cellulose-based Hydrogel Derived from Printed Waste Paper - Wong, Ru Sheong (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Hydrogels were prepared from regenerated cellulose dissolved in NaOH/urea solution by using epichlorohydrin (ECH) as a cross-linker, by two methods, which were freezing and heating. The structure and properties of hydrogel was characterised using SEM and water absorption testing. After NaOH and HCl pre-treatment, treated white printing waste paper was dissolved in NaOH/ Thiourea/Urea solution and regenerated using ethanol. Hydrogels prepared by heating method had better swelling ratio and reswelling kinetics than hydrogel prepared by freezing method. With the increase in cellulose concentration and ECH cross-linker, the swelling ratio of the hydrogels decreased, while the reswelling kinetics increased. Most of the hydrogels showed macroporous structure in SEM images. Heating hydrogels were more transparent compared to freezing hydrogels. Hence, structure and properties of hydrogels could be changed by varying the cellulose concentrations and ECH concentrations.